Navigating life after gastric cancer surgery: a qualitative exploration of the dyadic patient-caregiver perspective on quality of life outcomes - Gu, Yingying; Ma, Xiuxiu; Xin, Hanjia; Xiang, Ziying; Chen, Yanmei; He, Chaozhu (BMC cancer, 2025)
Gastric cancer (GC) families as a whole face the stressful time of cancer together, and the quality of life (QoL) of both the patient and the caregiver can be affected. Most past researchers have focused on the QoL of GC patients, but have neglected the role that caregivers play in the treatment process. The purpose of this study was to examine the factors influencing QoL of GC patients and their family caregivers, to compare the interactions and similarities and differences between the two influences, and to construct a conceptual model of the influences on QoL of GC patients and their caregivers based on the results of the study. This descriptive qualitative study was conducted in 2024 at two branches of a tertiary hospital in China, and participants were recruited by adopting a purposive sampling approach, where participants were patients with GC who met the criteria recommended by gastrointestinal surgeons and nurses, and caregivers were designated by patients. The sample was selected considering maximum differentiation, such as age, gender, cancer stage, and disease duration of the respondents. The sample size was based on data saturation with no new themes emerging. Based on the results of the pre-interviews, we made some adjustments to the interview format, i.e., interviewing some informants individually and others jointly. We used semi-structured interviews for data collection for the qualitative study, where participants were informed about the study, their roles, the risks and benefits of the study, and signed an informed consent form before the interviews began. In addition, the quality of field notes was assessed after each session. The process was the same for all interviews. To ensure the accuracy of the information, all information transmitted on paper was reviewed while listening to the recorded voice. We used directed content analysis to analyze the content of the interviews. A total of 30 patients and 26 caregivers were interviewed. Four themes emerged from the study, which were contextual factors (disease-specific factors, physical and social environments and individual and family characteristics), knowledge and belief factors (self symptom assessment and healthcare seeking behavior, health information delivery and accessibility, life priority adjustment), self-regulation factors (strategies for health behavior change, role adaptation and emotion regulation) and social facilitators (positive motivation and emotional support from family, friends, and society, missing companionship and challenges encountered by family and friends visiting the patient after surgery, caregiving burdens and challenges). In addition, the study confirmed a high correlation between the QoL of patients and caregivers. Our results address past gaps in the understanding of QoL for families with GC and update the concept of QoL by constructing a conceptual model of the factors that influence QoL for GC survivors and caregivers, as well as outlining the changes needed to improve health outcomes and QoL for survivors and their caregivers.